Analisis Implementasi Keselamatan dan Kesehatan Kerja pada Masa Pandemi COVID-19 Bagi Karyawan di Rumah Sakit X Kabupaten Karanganyar - Siti Hamurwani; Hanifa Maher Denny (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2021)
The world is currently facing the COVID-19 pandemic; therefore, the implementation of occupational safety and health (OSH) program in the hospital is very important to protect health care workers from the risk of being exposed to the COVID-19 disease. This study aimed to elucidate the implementation of the OSH program in preventing the transmission of COVID-19 to employees at Karanganyar District General Hospital. This research used qualitative methods. The researchers observed the study site, conducted in-depth interviews, and reviewed the documents. Seven informants were selected as informants, and then the information was triangulated to two subjects. The results showed that OSH's implementation in the study site complied with the Ministry of Health Guidelines for Hospital Services During New Adaptation, 2 November 2020. In terms of cultivating safety and health behavior at work, the hospital provided information and educational sessions. The morning briefing, a periodical reminder to implement safety and health, standing banners and posters, provision of guidelines and standards operating procedures were the pieces of evidence to prevent the transmission of COVID-19 in the hospital study site. The hospital emergency response team was part of the hospital's COVID-19 task force team. The facilities and enforcement of health protocols to prevent COVID-19 transmission in the study site were well established